Design Of Formula Varsity Race Car Suspension Upright - Suhaimi, Khalis; Mansor, Muhd Ridzuan; Mohd Rosli, Mohd Afzanizam; Abdul Kudus, Syahibudil Ikhwan; Salim, Mohd Azli; Shaharuzaman, Mohd Adrinata (2012)
This paper presents the design of a suspension upright for Formula Varsity race car. CATIA V5 R16 CAD software was utilized to generate the 3D model of the final upright design. Aluminum alloy grade 6061-T6 was selected for the upright construction material due to its low density and good mechanical strength as well as wide availability in different sizes. Structural analysis using finite element method (FEM) was implemented to analyze the structural strength. CATIA V5 Generative Structural Analysis workbench as used in the analysis. Results from the structural analysis shows that the upright design has a factor of safety of 12.1, which theoretically proved that the structure is able to perform safely as per design requirement. A part from that, through utilization of aluminum alloy as the upright material, the weight of the component is able to reduce up to 57.5% compared to the upright used in 2010 UTeM Formula Varsity race car. Thus, the new upright design is able to provide the crucial weight saving needed for an efficient race car without compromising its structural strength and safety.